Respon Pertumbuhan Bibit Kelapa Sawit (Elaeis guinensis Jacq) Yang diberi Pupuk Hijau Kirinyuh dan Pupuk NPK - Eko Teguh Wahyudi; Erlida Ariani; Sukemi Indra Saputra (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of research to know about the influence of giving kirinyuh green fertilizer interaction and little doses of NPK fertilizer along best treatment between kirinyuh green fertilizer with NPK fertilizer to palm oil seedling (Elaeis guineensis Jacq) growth on the main nursery. This research have done in the Garden of Agriculture Faculty, Riau University, Jl. Bina Widya KM 12,5 Simpang Baru, Tampan, Pekanbaru for about six months from december 2015 until mei 2016 with using Rancangan Acak Lengkap (RAL) Faktorial, there are two factors: first, Kirinyuh dose (K) had three levels, they area; K0=kirinyuh green fertilizer with 0 g/plant dose, K1= kirinyuh wet green fertilizer with 60 g/plant, K3= kirinyuh dry green fertilizer with 60 g/plant dose. Second, NPK fertilizer dose, it had three levels, they are; N0= giving NPK fertilizer with 0 g/plant dose N1=giving NPK fertilizer with 6,25 g/plant N2=giving NPK fertilizer with 12,5 g/plant. The parameter which to be subject are plant high, number of leaf, diameter of knot on tree, vast of leaf, wet plant weigh, dry root weigh, crown rasio and root. By statistic of analyse data with using kind exam and to be continue with different experience on level 5%. The result of experience shows that interaction of giving kirinyuh green fertilizer and NPK fertilizer could be influence with plant high,diameter of knot on tree, dry plant weigh amd the crown of root. With Combining on giving wet kirinyuh green fertilizer 60 g/plant doses and NPK fertilizer 12,5 g/plant are the best treatment. Keywords: Kirinyuh green fertilizer, NPK fertilizer, Palm Oil